Neutralization Of Oppositions of To the Paradigm of Cases In The Uzbek Language (Global Scientific Review, 2023)
The article will discuss neutralization, a phenomenon that arises as a result of the disappearance of signs of oppositions in certain speech conditions, and its influence on the morphological level of the Uzbek language, in particular, between members of the case paradigm.